2023
DOI: 10.1039/d2md00393g
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed late-stage diversification of macrocyclic nannocystins facilitating anticancer SAR and mode of action studies

Abstract: Nannocystins are a family of 21-membered cyclodepsipeptides with excellent anticancer activity. Yet their macrocyclic architecture poses a significant challenge to structure modification. Herein this issue has been addressed by leveraging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 91 publications
(169 reference statements)
0
2
0
Order By: Relevance
“…Informed by thus obtained SAR and pursuing a nannocystin-based fluorescent probe [93], we designed and synthesized a coumarin conjugate 58 with good cell permeability. It was observed by means of confocal fluorescent microscopy that this probe is localized predominantly to the endoplasmic reticulum (Figure 8C), most likely acting upon its target eEF1A at the ER-bound ribosome [90]. Interestingly, our result is in good agreement with a recent work that visualized eEF1A associated with the ribosome on the ER membrane at molecular resolution by the use of cryo-electron tomography [94], thereby shedding light on the intracellular mode of action of nannocystins.…”
Section: Natural Product Analoguessupporting
confidence: 91%
See 2 more Smart Citations
“…Informed by thus obtained SAR and pursuing a nannocystin-based fluorescent probe [93], we designed and synthesized a coumarin conjugate 58 with good cell permeability. It was observed by means of confocal fluorescent microscopy that this probe is localized predominantly to the endoplasmic reticulum (Figure 8C), most likely acting upon its target eEF1A at the ER-bound ribosome [90]. Interestingly, our result is in good agreement with a recent work that visualized eEF1A associated with the ribosome on the ER membrane at molecular resolution by the use of cryo-electron tomography [94], thereby shedding light on the intracellular mode of action of nannocystins.…”
Section: Natural Product Analoguessupporting
confidence: 91%
“…Aiming at site-directed late-stage diversification for quickly exploring chemical space around the nannocystin framework [89], we next remodeled its macrocycle composition in which a homochiral serine (highlighted in the structure) has been substituted for the innate D-serine to give the macrocyclic alcohol 57. To our satisfaction, the precursor 55 underwent smooth ring closure in a 70% yield under Heck coupling conditions, TBS deprotection then furnishing 57 ready for divergent post-macrocyclization esterification (Figure 8B) [90]. Although nannocystin A was shown to be a specific inhibitor of eukaryotic elongation factor 1A (eEF1A) [91], its exact anticancer mode of action awaits further elucidation [92].…”
Section: Natural Product Analoguesmentioning
confidence: 89%
See 1 more Smart Citation
“…Aside from target elucidation and SAR profiling, the exact mechanism of nannocystins is a subject of enduring interest [ 90 , 91 , 92 ] given the poorly understood role of eEF1A in tumorigenesis. Chen et al showed that the antimetastatic effect of nannocystin Ax in lung cancer cells is attributable to its interference with the TGF-β/Smad signaling pathway [ 90 ].…”
Section: Recent Advances In Anticancer Eef1a-targeting Agentsmentioning
confidence: 99%
“…Therefore, similar to the case of plitidepsin [ 30 ], the possibility that nannocystins impact certain protumorigenic pathway(s) mediated by eEF1A cannot be ruled out. Recently, we designed a serine-incorporating nannocystin 14 ( Figure 4 ) to leverage a post-macrocyclization diversification strategy for efficient side-chain variation [ 92 ]. Thus obtained SAR concurred with the general trend depicted in Figure 4 and further informed the development of a coumarin-conjugated fluorescent probe 15 .…”
Section: Recent Advances In Anticancer Eef1a-targeting Agentsmentioning
confidence: 99%